Manufacturing method of polarizing film and polarizing film

By using a PVA film with silicon-containing groups and ethylene units in the manufacturing process, the challenges of achieving high optical performance and low shrinkage stress in optical films are addressed, allowing for efficient production at lower stretching temperatures.

JP7653448B2Active Publication Date: 2025-03-28KURARAY CO LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2022560647
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-11-09
Filing Date
2021-08-10
Publication Date
2025-03-28
Estimated Expiration
2041-08-10

AI Technical Summary

Technical Problem

Existing methods for manufacturing optical films with high optical performance and low shrinkage stress face challenges, particularly when using PVA films with high degrees of polymerization, as they require increased stretching temperatures, which is undesirable for industrial production.

Method used

A film for manufacturing optical films comprising PVA with silicon-containing groups and ethylene units, where the silicon-containing groups can convert to silanol groups, and the content of these groups is between 0.01 mol % and 1.0 mol %, and the ethylene unit content is between 0.5 mol % and 10 mol %, allowing for improved optical performance without increasing the stretching temperature.

Benefits of technology

The proposed solution enables the production of optical films with excellent optical performance and controlled shrinkage stress, while maintaining a lower stretching temperature, thus addressing the industrial production challenges associated with high polymerization degree PVA films.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007653448000004
    Figure 0007653448000004
  • Figure 0007653448000005
    Figure 0007653448000005
  • Figure 0007653448000001
    Figure 0007653448000001
Patent Text Reader

Abstract

Provided are: a film for producing an optical film, which can give an optical film which exhibits excellent optical performance and in which an increase in stretching temperature is suppressed in a case where an optical film having a similar shrinkage stress is produced; a method for producing an optical film using this type of film for producing an optical film; and an optical film. The present invention is a film for producing an optical film, which contains a poly(vinyl alcohol) having a silicon-containing group and an ethylene unit. The silicon-containing group is a silanol group or a group that can be converted into a silanol group in the presence of water. The content of the silicon-containing group is 0.01-1.0 mol% and the content of the ethylene unit is 0.5-10 mol%, each relative to the total amount of structural units in the poly(vinyl alcohol).
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a film for producing an optical film, a method for producing an optical film, and an optical film. [Background technology]

[0002] Polarizing plates, which have the function of transmitting and blocking light, are basic components of liquid crystal displays (LCDs) along with liquid crystals, which change the polarization state of light. Most polarizing plates have a structure in which a protective film such as a triacetate cellulose (TAC) film is laminated to the surface of a polarizing film. Polarizing films are made by uniaxially stretching a polyvinyl alcohol film (hereinafter, "polyvinyl alcohol" may be abbreviated as "PVA") and adding an iodine-based dye (I 3 - or I 5 - The mainstream is those that adsorb dichroic pigments such as dichroic organic dyes.

[0003] LCDs are used in a wide range of applications, including small devices such as calculators and wristwatches, smartphones, notebook computers, LCD monitors, LCD color projectors, LCD televisions, car navigation systems, mobile phones, and measuring instruments used indoors and outdoors. In response to the recent increase in performance of LCDs, there is a demand for higher performance of polarizing plates, which are components of LCDs. Specifically, there is a demand for polarizing plates that have better optical performance and excellent dimensional stability even at high temperatures. Therefore, there is a demand for polarizing films used in polarizing plates that have better optical performance (polarizing performance) and small shrinkage stress at high temperatures.

[0004] However, it is not easy to reduce the shrinkage stress at high temperatures while improving the optical performance (polarization performance) of polarizing films. This is because there is generally a trade-off between the polarization performance and shrinkage stress of polarizing films. In other words, if you try to increase the polarization performance of a polarizing film, the shrinkage stress increases, and if you try to decrease the shrinkage stress, the polarization performance decreases.

[0005] Patent Document 1 discloses a polarizing film with improved optical performance and moist heat resistance, which uses PVA having a degree of polymerization of at least 2500. In Patent Document 1, a film is formed using a PVA film-forming solution in which PVA having a high degree of polymerization, such as 4980, is dissolved in a solvent mainly composed of dimethyl sulfoxide. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Japanese Patent Application Publication No. 1-105204 Summary of the Invention [Problem to be solved by the invention]

[0007] In the industrial production of PVA films, it is common to use a PVA aqueous solution in which water is used as a solvent as a film-forming solution, taking into consideration environmental aspects, economics, and the like. However, when a PVA having a high degree of polymerization is used as in Patent Document 1, the viscosity of the PVA aqueous solution increases, so that the film-forming property of the PVA film is poor, which is not preferable for industrial production. Therefore, a method for improving the optical performance of an optical film by a method other than a method for increasing the polymerization degree of PVA is desired. In addition, when the production conditions (stretching conditions) of the optical film are the same, an optical film obtained from a PVA film having a PVA with a high degree of polymerization has a higher shrinkage stress than a PVA film having a PVA with a low degree of polymerization. Therefore, when a PVA film having a PVA with a high degree of polymerization is used, in order to obtain an optical film having excellent optical performance and small shrinkage stress, it is necessary to increase the stretching temperature when producing the optical film, which is not preferable for industrial production. Therefore, even when a PVA film having a PVA with a high degree of polymerization is used, a method for obtaining an optical film having excellent optical performance without increasing the stretching temperature when producing the optical film is desired.

[0008] The present inventors have found that the use of a PVA film containing a PVA having a silicon-containing group can suppress the increase in viscosity of the PVA aqueous solution, while significantly improving the optical performance of the resulting optical film. However, even when a PVA film containing a PVA having a silicon-containing group is used, it is still necessary to increase the stretching temperature during the production of the optical film.

[0009] The present invention has been made in light of the above-mentioned circumstances, and has an object to provide a film for producing an optical film that can suppress an increase in the stretching temperature and produce an optical film with excellent optical performance when producing an optical film with a similar shrinkage stress, a method for producing an optical film using such a film for producing an optical film, and an optical film. [Means for solving the problem]

[0010] The above objectives are: [1] A film for producing an optical film, comprising PVA having a silicon-containing group and an ethylene unit, the silicon-containing group being a silanol group or a group that can be converted into a silanol group in the presence of water, the content of the silicon-containing group relative to all structural units in the PVA being 0.01 mol % or more and 1.0 mol % or less, and the content of the ethylene unit being 0.5 mol % or more and 10 mol % or less; [2] The film for producing an optical film according to [1], wherein the PVA has a viscosity average degree of polymerization of 1,000 or more and 6,000 or less, and a degree of saponification of 98.7 mol % or more; [3] The film for producing an optical film according to [2], wherein the product of the viscosity average degree of polymerization and the content of the silicon-containing group is 100 mol % or more and 2,000 mol % or less; [4] A film for producing an optical film according to any one of [1] to [3], having an average thickness of 1 μm or more and 75 μm or less; [5] A film for producing an optical film according to any one of [1] to [4], having a degree of swelling of 140% or more and 400% or less; [6] The film for producing an optical film according to any one of [1] to [5], wherein the optical film is a polarizing film; [7] A film for producing an optical film according to any one of [1] to [6], which is a non-stretched film; [8] A method for producing an optical film, comprising a step of uniaxially stretching the film for optical film production according to any one of [1] to [7]; [9] The method for producing an optical film according to [8], wherein the optical film is a polarizing film;

[10] An optical film comprising a PVA having a silicon-containing group and an ethylene unit, the silicon-containing group being a silanol group or a group that can be converted into a silanol group in the presence of water, the content of the silicon-containing group relative to all structural units in the PVA being 0.01 mol % or more and 1.0 mol % or less, and the content of the ethylene unit being 0.5 mol % or more and 10 mol % or less;

[11] Shrinkage stress is 100N / m 2 The optical film of

[10] is as follows:

[12] The optical film according to

[10] or

[11] , which is a polarizing film; and

[13] Any of the optical films

[10] to

[12] which are single-layer films; This is achieved by providing either Effect of the Invention

[0011] According to the present invention, when producing an optical film having the same degree of shrinkage stress, it is possible to provide a film for producing an optical film that can suppress an increase in the stretching temperature and obtain an optical film having excellent optical performance, a method for producing an optical film using such a film for producing an optical film, and an optical film. In other words, according to the film for producing an optical film and the method for producing an optical film of the present invention, it is possible to suppress an increase in shrinkage stress and an increase in the stretching temperature while improving the optical performance of the obtained optical film. [Brief description of the drawings]

[0012] [Figure 1] FIG. 1 is a graph in which the stretching temperature at which the shrinkage stress of each of the polarizing films obtained in Examples 1 to 3 and Comparative Examples 1 to 5 reached 75 N / mm 2 is plotted against the dichroic ratio at that time. [Diagram 2] FIG. 2 is a graph in which the stretching temperature at which the shrinkage stress of each of the polarizing films obtained in Example 3 and Comparative Examples 1, 4, and 5 reached 75 N / mm 2 is plotted against the dichroic ratio at that time. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] <Film for optical film manufacturing> The film for producing an optical film of the present invention contains polyvinyl alcohol having a silicon-containing group and an ethylene unit (hereinafter, sometimes referred to as "modified PVA").

[0014] (Modified PVA) Modified PVA consists of vinyl alcohol units (-CH 2It is a polymer having a structural unit of -CH(OH)-, and also has a silicon-containing group and an ethylene unit. The modified PVA may further have a vinyl ester unit such as a vinyl acetate unit or other structural unit.

[0015] The lower limit of the viscosity average polymerization degree of the modified PVA is preferably 1,000, more preferably 2,000, and even more preferably 2,500. When the viscosity average polymerization degree of the modified PVA is equal to or higher than the lower limit, the film for optical film production of the present invention has excellent stretching processability, and an optical film having higher optical performance and good wet heat resistance can be obtained. On the other hand, the upper limit of the viscosity average polymerization degree is preferably 6,000, more preferably 5,000, and even more preferably 4,000. When the viscosity average polymerization degree of the modified PVA is equal to or lower than the upper limit, good water solubility is exhibited, and an increase in the viscosity of the aqueous solution is suppressed. In addition, when the viscosity average polymerization degree of the modified PVA is equal to or lower than the upper limit, the stretching temperature is further suppressed from being raised. Therefore, when the viscosity average polymerization degree of the modified PVA is equal to or lower than the upper limit, good film formability is exhibited, and the productivity of the film for optical film production of the present invention can be increased. Furthermore, when the viscosity average degree of polymerization of the modified PVA is equal to or less than the upper limit, an optical film in which an increase in shrinkage stress is suppressed can be easily obtained from the film for producing an optical film of the present invention.

[0016] The viscosity average degree of polymerization means the average degree of polymerization measured in accordance with the description of JIS K6726-1994. That is, in this specification, the viscosity average degree of polymerization is calculated from the intrinsic viscosity [η] (unit: deciliter / g) measured in water at 30° C. after resaponifying the remaining vinyl ester groups of PVA and purifying it, according to the following formula: Viscosity average degree of polymerization Po=([η]×10 4 / 8.29) (1 / 0.62)

[0017] The lower limit of the saponification degree of the modified PVA is preferably 98.7 mol%, more preferably 99.0 mol%, even more preferably 99.5 mol%, even more preferably 99.8 mol%, and particularly preferably 99.9 mol%. By having a saponification degree of the modified PVA or more, an optical film having better optical performance and moist heat resistance can be obtained. On the other hand, there is no particular limit to the upper limit of the saponification degree, but from the viewpoint of productivity of the modified PVA, it is preferably 99.99 mol% or less.

[0018] The degree of saponification of PVA refers to the ratio (mol%) of the number of moles of vinyl alcohol units to the total number of moles of structural units (typically vinyl ester units) that can be converted to vinyl alcohol units by saponification that PVA has, and vinyl alcohol units. The degree of saponification of PVA can be measured according to the description of JIS K6726-1994.

[0019] The modified PVA has a silicon-containing group. This silicon-containing group is a silanol group or a group that can be converted to a silanol group in the presence of water. The silanol group refers to a group having a silicon atom and at least one hydroxyl group bonded to the silicon atom. The number of hydroxyl groups in the silanol group is usually 1 to 3, and preferably 3. The hydroxyl group in the silanol group may be present in the form of a salt (e.g., -ONa, -OK, etc.).

[0020] The group that can be converted to a silanol group in the presence of water means a group that can be converted to a silanol group when PVA is heated in water under conditions of a reaction time of 2 hours and a reaction temperature of 150°C. This conversion to a silanol group may occur by hydrolysis. Examples of groups that can be converted to a silanol group in the presence of water include groups in which at least one alkoxy group or acyloxy group is bonded to a silicon atom, and specific examples thereof include a trimethoxysilyl group, a triethoxysilyl group, a triisopropoxysilyl group, a dimethoxymethylsilyl group, a diethoxymethylsilyl group, a methoxydimethylsilyl group, an ethoxydimethylsilyl group, and a triacetoxysilyl group.

[0021] Examples of the silicon-containing group, i.e., a silanol group or a group that can be converted to a silanol group in the presence of water, include groups represented by any of the following formulas (1) to (3). Among these, the group represented by the following formula (1) is preferred.

[0022] [ka]

[0023] In formulas (1) to (3), R 1 R are each independently a hydrogen atom, a substituted or unsubstituted hydrocarbon group having 1 to 20 carbon atoms, or a substituted or unsubstituted acyl group having 1 to 20 carbon atoms. 2 are each independently a substituted or unsubstituted hydrocarbon group having 1 to 20 carbon atoms.

[0024] R 1 and R 2 Examples of the hydrocarbon group having 1 to 20 carbon atoms represented by the formula (I) include aliphatic hydrocarbon groups, alicyclic hydrocarbon groups (cyclohexyl group, etc.), and aromatic hydrocarbon groups (phenyl group, etc.), with aliphatic hydrocarbon groups being preferred. Examples of the aliphatic hydrocarbon group include alkyl groups such as methyl, ethyl, and propyl groups, alkenyl groups such as vinyl groups, and alkynyl groups such as ethynyl groups, with alkyl groups being preferred. 1 and R 2 The number of carbon atoms in the hydrocarbon group represented by R is preferably 1 to 6, and more preferably 1 to 3. 1 and R 2 At least a portion of the hydrogen atoms of the hydrocarbon group represented by the following formula may be substituted with a halogen atom, a carboxy group, an alkoxy group (such as a methoxy group or an ethoxy group), or the like.

[0025] R 1Examples of the acyl group having 1 to 20 carbon atoms represented by the formula (I) include a group in which a carbonyl group (-CO-) is bonded to a hydrogen atom or a hydrocarbon group having 1 to 19 carbon atoms. The hydrocarbon group having 1 to 19 carbon atoms is preferably an aliphatic hydrocarbon group, more preferably an alkyl group. Specific examples of the acyl group include a formyl group, an acetyl group, a propionyl group, and a benzoyl group. R 1 The number of carbon atoms in the acyl group represented by R is preferably 1 to 6, and more preferably 1 to 3. 1 At least a portion of the hydrogen atoms of the acyl group represented by the following formula may be substituted with a halogen atom, a carboxy group, an alkoxy group (such as a methoxy group), or the like.

[0026] In the group represented by any one of the formulas (1) to (3), R 1 When at least one of R is a hydrogen atom, the group is a silanol group. 1 When R is not a hydrogen atom, this group is a group that can be converted to a silanol group in the presence of water. 1 is preferably a hydrogen atom or a substituted or unsubstituted hydrocarbon group having 1 to 20 carbon atoms.

[0027] From the viewpoint of the optical performance of the resulting optical film, it is preferred that the silicon-containing group is directly bonded to a carbon atom in the polymer main chain via a silicon-carbon bond.

[0028] The content of silicon-containing groups relative to all structural units in the modified PVA is 0.01 mol% or more and 1.0 mol% or less. In this way, by using a modified PVA having a predetermined amount of silicon-containing groups, the optical performance of the obtained optical film is improved. The lower limit of the content of silicon-containing groups in the modified PVA is 0.01 mol%, preferably 0.05 mol%, more preferably 0.1 mol%, and in some cases, even more preferably 0.15 mol%. By making the content of silicon-containing groups equal to or more than the lower limit, the optical performance of the obtained optical film can be sufficiently improved. On the other hand, the upper limit of the content of silicon-containing groups relative to all structural units in the modified PVA is 1.0 mol%, preferably 0.8 mol%, more preferably 0.6 mol%, and even more preferably 0.4 mol%. By making the content of silicon-containing groups equal to or less than the upper limit, the water solubility of the modified PVA and the viscosity stability of the aqueous solution are improved, and film productivity (film formability) can be improved. Furthermore, by controlling the content of the silicon-containing group to the above upper limit or less, it is also possible to prevent the stretching temperature from becoming too high.

[0029] In the modified PVA, the content (mol%) of silicon-containing groups can be determined, for example, from proton NMR of the vinyl ester polymer before saponification. Here, when measuring the proton NMR of the vinyl ester polymer before saponification, the vinyl ester polymer is purified by reprecipitation with hexane-acetone to completely remove unreacted monomers from the polymer, then dried at 90°C under reduced pressure for 2 days, and then analyzed by CDCl. 3 The sample is dissolved in a solvent and subjected to analysis.

[0030] The lower limit of the product of the viscosity average polymerization degree of the modified PVA and the content of the silicon-containing group is preferably 100 mol%, more preferably 200 mol%, even more preferably 300 mol%, and even more preferably 400 mol%. When the product is equal to or greater than the lower limit, the optical performance of the obtained optical film is more excellent. On the other hand, the upper limit of the product is preferably 2,000 mol%, more preferably 1,500 mol%, even more preferably 1,200 mol%, and particularly preferably 800 mol%. When the product is equal to or less than the upper limit, the water solubility of the modified PVA is increased and the stretching temperature is further suppressed from increasing, so that the productivity of the film for producing the optical film can be further increased.

[0031] The modified PVA preferably has a structural unit having a silicon-containing group. An example of the structural unit having a silicon-containing group is a structural unit represented by the following formula (4).

[0032] [ka]

[0033] In formula (4), R 3 R is a hydrogen atom or a methyl group. 4 R is a single bond or a divalent linking group. 5 is a silicon-containing group.

[0034] R 3 is preferably a hydrogen atom.

[0035] R 4 The divalent linking group represented by the formula: -(CH 2 ) n -(n is an integer from 1 to 5) or -CONR 6 -R 7 -(R 6 R is a hydrogen atom or an alkyl group having 1 to 5 carbon atoms. 7 is the above-mentioned -(CH 2 ) n-, or a divalent hydrocarbon group containing at least one of an oxygen atom and a nitrogen atom.

[0036] The divalent hydrocarbon group containing at least one of an oxygen atom and a nitrogen atom is, for example, -CH 2 CH 2 NHCH 2 CH 2 CH 2 -, -CH 2 CH 2 NHCH 2 CH 2 -, -CH 2 CH 2 NHCH 2 -, -CH 2 CH 2 N(CH 3 )CH 2 CH 2 -, -CH 2 CH 2 N(CH 3 )CH 2 -, -CH 2 CH 2 OCH 2 CH 2 CH 2 -, -CH 2 CH 2 OCH 2 CH 2 -, -CH 2 CH 2 OCH 2 The divalent hydrocarbon group containing at least one of an oxygen atom and a nitrogen atom may have, for example, 2 or more and 6 or less carbon atoms.

[0037] R 4 is preferably a single bond.

[0038] R 5 Specific examples of the silicon-containing group represented by the formula are as described above, and include the groups represented by any one of the formulas (1) to (3), with the group represented by the formula (1) being preferred.

[0039] The number of silicon-containing groups contained in the structural unit having a silicon-containing group is not particularly limited, but may be 1. The range of the content of the structural unit having a silicon-containing group relative to the total structural units in the modified PVA may be within the range of the content of the silicon-containing group described above. In addition, the range of the product of the viscosity average polymerization degree and the content of the structural unit having a silicon-containing group of the modified PVA may be within the range of the product of the viscosity average polymerization degree and the content of the silicon-containing group described above.

[0040] Modified PVA further contains ethylene units (-CH 2 -CH 2 -). The content of ethylene units relative to all structural units in the modified PVA is 0.5 mol% or more and 10 mol% or less. In this way, by using a modified PVA having a predetermined amount of ethylene units, an optical film having excellent optical performance while suppressing an increase in the stretching temperature can be obtained. The lower limit of the content of ethylene units is preferably 1.0 mol%, more preferably 2.0 mol%. By setting the content of ethylene units to the lower limit or more, it is possible to further suppress an increase in the stretching temperature. On the other hand, the upper limit of the content of ethylene units is preferably 6 mol%, more preferably 5 mol%, and even more preferably 4.5 mol%. By setting the content of ethylene units to the upper limit or less, it is possible to increase the water solubility of the modified PVA.

[0041] The content of ethylene units in the modified PVA can be determined, for example, by proton NMR. For example, in the same manner as the content of the silicon-containing groups described above, the ethylene unit content of the modified PVA can be determined by measuring the modified vinyl ester polymer, which is the precursor of the modified PVA, by proton NMR.

[0042] The modified PVA may have other structural units than vinyl alcohol units, vinyl ester units, structural units having silicon-containing groups, and ethylene units. However, the content of the other structural units relative to the total structural units of the modified PVA is preferably 15 mol% or less, more preferably 5 mol% or less, even more preferably 1 mol% or less, and even more preferably 0.1 mol% or less in some cases. When the modified PVA is substantially composed of vinyl alcohol units, vinyl ester units, structural units having silicon-containing groups, and structural units having ethylene units, the effects of the present invention may be more fully achieved.

[0043] The film for producing an optical film may contain one type of modified PVA alone, or may contain two or more types of modified PVA differing from each other in the degree of polymerization, degree of saponification, content of silicon-containing groups, content of ethylene units, etc.

[0044] The lower limit of the content of the modified PVA in the film for producing an optical film is not particularly limited, but is preferably 50% by mass, more preferably 80% by mass, and even more preferably 85% by mass. By making the content of the modified PVA equal to or greater than the lower limit, the effects of the present invention can be further enhanced. On the other hand, the upper limit of the content is not particularly limited, and may be 100% by mass, preferably 99% by mass, and more preferably 95% by mass. The content (mass%) of each component in the film for producing an optical film is based on the dry state, i.e., the total content of all components other than water.

[0045] (Method of manufacturing modified PVA) The method for producing the modified PVA is not particularly limited. For example, the modified PVA can be produced by copolymerizing a vinyl ester monomer, a monomer having a silicon-containing group, and ethylene, and saponifying the resulting vinyl ester polymer.

[0046] Examples of vinyl ester monomers include vinyl formate, vinyl acetate, vinyl propionate, vinyl valerate, vinyl caprate, vinyl laurate, vinyl stearate, vinyl benzoate, vinyl pivalate, vinyl versatate, etc. Among these, vinyl acetate is preferred.

[0047] Examples of monomers having a silicon-containing group include vinyltrimethoxysilane, vinylmethyldimethoxysilane, vinyldimethylmethoxysilane, vinyltriethoxysilane, vinylmethyldiethoxysilane, vinyldimethylethoxysilane, allyltrimethoxysilane, allylmethyldimethoxysilane, allyldimethylmethoxysilane, allyltriethoxysilane, allylmethyldiethoxysilane, allyldimethylethoxysilane, vinyltris(β-methoxyethoxy)silane, vinylisobutyldimethoxysilane, and vinylethyldimethoxysilane. , vinyl methoxydibutoxysilane, vinyl dimethoxybutoxysilane, vinyl tributoxysilane, vinyl methoxydihexyloxysilane, vinyl dimethoxyhexyloxysilane, vinyl trihexyloxysilane, vinyl methoxydioctyloxysilane, vinyl dimethoxyoctyloxysilane, vinyl trioctyloxysilane, vinyl methoxydilauryloxysilane, vinyl dimethoxylauryloxysilane, vinyl methoxydioleyloxysilane, vinyl dimethoxyoleyloxysilane, 3-(meth)acrylamide-propyl trimethoxy Silane, 3-(meth)acrylamido-propyltriethoxysilane, 3-(meth)acrylamido-propyltri(β-methoxyethoxy)silane, 2-(meth)acrylamido-ethyltrimethoxysilane, 1-(meth)acrylamido-methyltrimethoxysilane, 2-(meth)acrylamido-2-methylpropyltrimethoxysilane, 2-(meth)acrylamido-isopropyltrimethoxysilane, N-(2-(meth)acrylamido-ethyl)-aminopropyltrimethoxysilane, (3-(meth)acrylamido-propyl N-(2-(meth)acrylamide-ethyl)-oxypropyltrimethoxysilane, 3-(meth)acrylamide-propyltriacetoxysilane, 2-(meth)acrylamide-ethyltriacetoxysilane, 4-(meth)acrylamide-butyltriacetoxysilane, 3-(meth)acrylamide-propyltripropionyloxysilane, 2-(meth)acrylamide-2-methylpropyltriacetoxysilane, N-(2-(meth)acrylamide-ethyl)-aminopropyltriacetoxysilane, 3-(meth)acrylamide-propylisobutyldimethoxysilane,Examples of the silane include 2-(meth)acrylamide-ethyldimethylmethoxysilane, 3-(meth)acrylamide-propylmethyldiacetoxysilane, 2-(meth)acrylamide-2-methylpropylhydrogendimethoxysilane, 3-(N-methyl-(meth)acrylamide)-propyltrimethoxysilane, and 2-(N-ethyl-(meth)acrylamide)-ethyltriacetoxysilane.

[0048] The method of copolymerizing the vinyl ester monomer, the monomer having a silicon-containing group, and ethylene is not particularly limited, and includes known methods such as bulk polymerization, solution polymerization, suspension polymerization, and emulsion polymerization.Among these methods, the bulk polymerization carried out without a solvent and the solution polymerization carried out using a solvent such as alcohol are preferred.The solvent used as the solvent during solution polymerization includes esters such as methyl acetate and ethyl acetate; aromatic hydrocarbons such as benzene and toluene; and lower alcohols such as methanol and ethanol.

[0049] The initiator used in the copolymerization reaction is appropriately selected from conventionally known azo initiators, peroxide initiators, redox initiators, etc. Examples of the azo initiator include 2,2'-azobisisobutyronitrile, 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), etc. Examples of peroxide initiators include percarbonate compounds such as di-normal propyl peroxydicarbonate, diisopropyl peroxydicarbonate, di-2-ethylhexyl peroxydicarbonate, and diethoxyethyl peroxydicarbonate; perester compounds such as t-butyl peroxyneodecanate, α-cumyl peroxyneodecanate, and t-butyl peroxyneodecanate; acetylcyclohexylsulfonyl peroxide, diisobutyryl peroxide; and 2,4,4-trimethylpentyl-2-peroxyphenoxyacetate. Furthermore, the above-listed peroxide initiators can be combined with potassium persulfate, ammonium persulfate, hydrogen peroxide, and the like to form an initiator. Examples of redox initiators include combinations of the above-listed peroxides with reducing agents such as sodium hydrogen sulfite, sodium hydrogen carbonate, tartaric acid, L-ascorbic acid, and Rongalite.

[0050] The polymerization temperature when carrying out the copolymerization reaction is not particularly limited, but is preferably from 0°C to 180°C, more preferably from 20°C to 160°C, and even more preferably from 30°C to 150°C.

[0051] As a method for producing a vinyl ester polymer, it is preferable to copolymerize ethylene under pressure in the presence of a vinyl ester monomer and a monomer having a silicon-containing group. The ethylene pressure in the polymerization reactor is not particularly limited, but is preferably 0.01 to 2.0 MPa, more preferably 0.05 to 1.0 MPa, and in some cases, is even more preferably 0.1 to 0.65 MPa. The polymerization rate of the vinyl ester monomer at the outlet of the polymerization reactor is not particularly limited, but is preferably 5 to 90%, and in some cases, is even more preferably 15 to 85%.

[0052] When copolymerizing a vinyl ester monomer, a monomer having a silicon-containing group, and ethylene, other copolymerizable monomers can be copolymerized as necessary within a range that does not impair the effects of the present invention.Examples of other monomers include olefins having 3 to 30 carbon atoms, such as propylene, 1-butene, and isobutene; acrylic acid or a salt thereof; acrylic acid esters, such as methyl acrylate, ethyl acrylate, n-propyl acrylate, i-propyl acrylate, n-butyl acrylate, i-butyl acrylate, t-butyl acrylate, 2-ethylhexyl acrylate, dodecyl acrylate, and octadecyl acrylate; methacrylic acid or a salt thereof; methyl methacrylate, ethyl methacrylate, and n-propyl methacrylate. methacrylic acid esters such as i-propyl methacrylate, n-butyl methacrylate, i-butyl methacrylate, t-butyl methacrylate, 2-ethylhexyl methacrylate, dodecyl methacrylate, and octadecyl methacrylate; acrylamide, N-methylacrylamide, N-ethylacrylamide, N,N-dimethylacrylamide, diacetone acrylamide, acrylamidopropanesulfonic acid or a salt thereof, acrylamidopropyldimethylamine or a salt thereof, N-methylolacrylamide or a salt thereof, methacrylamide derivatives such as methacrylamide, N-methyl methacrylamide, N-ethyl methacrylamide, methacrylamide propanesulfonic acid or a salt thereof, methacrylamide propyl dimethylamine or a salt thereof, N-methylol methacrylamide or a derivative thereof; N-vinyl amides such as N-vinyl formamide, N-vinyl acetamide, and N-vinyl pyrrolidone; vinyl ethers such as methyl vinyl ether, ethyl vinyl ether, n-propyl vinyl ether, i-propyl vinyl ether, n-butyl vinyl ether, i-butyl vinyl ether, t-butyl vinyl ether, dodecyl vinyl ether, and stearyl vinyl ether; vinyl cyanides such as acrylonitrile and methacrylonitrile; vinyl halides such as vinyl chloride, vinylidene chloride, vinyl fluoride, and vinylidene fluoride; allyl compounds such as allyl acetate and allyl chloride; maleic acid or a salt, ester, or acid anhydride thereof; itaconic acid or a salt, ester, or acid anhydride thereof; and isopropenyl acetate. The vinyl ester polymer may have structural units derived from one or more of the other monomers mentioned above.

[0053] The proportion of the structural units derived from the other monomers (vinyl ester monomers, monomers having a silicon-containing group, and monomers other than ethylene) in the vinyl ester polymer is not necessarily limited as long as it does not impede the effects of the present invention, but is preferably 15 mol % or less, more preferably 5 mol % or less, even more preferably 1 mol % or less, and in some cases even more preferably 0.1 mol % or less, based on the number of moles of all structural units constituting the vinyl ester polymer.

[0054] The vinyl ester polymer is then saponified in a solvent according to a known method to obtain a modified PVA. The solvent used in the saponification reaction is preferably an alcohol. Examples of the alcohol include lower alcohols such as methanol and ethanol, and methanol is particularly preferably used. The solvent used in the saponification reaction may further contain an organic solvent such as acetone, esters such as methyl acetate and ethyl acetate, and toluene in addition to the alcohol. Examples of the catalyst used in the saponification reaction include alkali metal hydroxides such as potassium hydroxide and sodium hydroxide, alkali catalysts such as sodium methylate, and acid catalysts such as mineral acids. The temperature of the saponification reaction can be, for example, 20°C or higher and 60°C or lower. When a gel-like product precipitates as the saponification reaction proceeds, the product is crushed at that point, washed, and then dried to obtain a modified PVA.

[0055] (Plasticizer) The film for optical film production of the present invention preferably contains a plasticizer. When the film for optical film production contains a plasticizer, the stretchability can be increased. The plasticizer is preferably a polyhydric alcohol. Examples of the polyhydric alcohol include ethylene glycol, glycerin, propylene glycol, diethylene glycol, diglycerin, triethylene glycol, tetraethylene glycol, and trimethylolpropane. Among these, glycerin is preferred from the viewpoint of improving the stretchability. One or more kinds of plasticizers can be used.

[0056] The lower limit of the content of the plasticizer in the film for optical film production of the present invention is preferably 1 part by mass, more preferably 3 parts by mass, and even more preferably 5 parts by mass, relative to 100 parts by mass of the modified PVA. By having the content of the plasticizer be equal to or greater than the lower limit, the stretchability of the film is improved, and the optical performance of the obtained optical film can be further improved. On the other hand, the upper limit of the content of the plasticizer is preferably 20 parts by mass, more preferably 17 parts by mass, and even more preferably 15 parts by mass, relative to 100 parts by mass of the modified PVA. By having the content of the plasticizer be equal to or less than the upper limit, it is possible to prevent the film from becoming too flexible and the handling properties from being reduced.

[0057] (Surfactant) The optical film-producing film preferably contains a surfactant. By forming a film using a film-forming solution containing a surfactant, the film-forming properties are improved, the occurrence of unevenness in the film thickness is suppressed, and the film is easily peeled off from a metal roll or belt used in film formation. When a film for optical film production is produced from a film-forming solution containing a surfactant, the resulting film may contain a surfactant.

[0058] The type of surfactant is not particularly limited, but from the viewpoint of releasability from a metal roll or belt, anionic surfactants and nonionic surfactants are preferred.

[0059] Examples of anionic surfactants include carboxylic acid types such as potassium laurate; sulfate types such as polyoxyethylene lauryl ether sulfate and octyl sulfate; and sulfonic acid types such as dodecylbenzenesulfonate.

[0060] Examples of nonionic surfactants include alkyl ether types such as polyoxyethylene oleyl ether; alkyl phenyl ether types such as polyoxyethylene octylphenyl ether; alkyl ester types such as polyoxyethylene laurate; alkyl amine types such as polyoxyethylene lauryl amino ether; alkyl amide types such as polyoxyethylene lauric acid amide; polypropylene glycol ether types such as polyoxyethylene polyoxypropylene ether; alkanolamide types such as lauric acid diethanolamide and oleic acid diethanolamide; and allyl phenyl ether types such as polyoxyalkylene allyl phenyl ether.

[0061] The surfactants can be used alone or in combination of two or more.

[0062] When the film for optical film production contains a surfactant, the lower limit of the content is preferably 0.01 parts by mass, more preferably 0.02 parts by mass, and even more preferably 0.05 parts by mass, relative to 100 parts by mass of modified PVA. By making the content of the surfactant equal to or greater than the lower limit, film formability and peelability are further improved. On the other hand, the upper limit of the content is preferably 0.5 parts by mass, more preferably 0.3 parts by mass, and even more preferably 0.1 parts by mass, relative to 100 parts by mass of modified PVA. By making the content of the surfactant equal to or less than the upper limit, it is possible to prevent the surfactant from bleeding out onto the surface of the film, causing blocking and reducing the handleability.

[0063] (Other additives, etc.) The film for producing an optical film of the present invention may further contain additives, such as a filler, a processing stabilizer such as a copper compound, a weather resistance stabilizer, a colorant, an ultraviolet absorber, a light stabilizer, an antioxidant, an antistatic agent, a flame retardant, other thermoplastic resins, a lubricant, a fragrance, an antifoaming agent, a deodorant, an extender, a peeling agent, a releasing agent, a reinforcing agent, a crosslinking agent, a mildew inhibitor, a preservative, and a crystallization rate retarder, as necessary.

[0064] The film for optical film production of the present invention may contain a PVA other than the modified PVA described above. The total content of all PVAs including modified PVA, plasticizers and surfactants in the film for optical film production of the present invention is preferably 80% by mass or more, more preferably 90% by mass or more, even more preferably 95% by mass or more, and even more preferably 99% by mass or more in some cases. When the film for optical film production of the present invention is substantially composed of PVA, plasticizer and surfactant, the effects of the present invention can be more fully exhibited.

[0065] The content of the modified PVA with respect to all the PVA contained in the film for producing an optical film of the present invention is preferably 50% by mass or more, more preferably 80% by mass or more, more preferably 90% by mass or more, even more preferably 95% by mass or more, and even more preferably 99% by mass or more. By mainly using the modified PVA as the PVA in the film for producing an optical film of the present invention, the effects of the present invention can be more fully exhibited.

[0066] The total content of the modified PVA, plasticizer, and surfactant in the film for producing an optical film of the present invention is preferably 80% by mass or more, more preferably 90% by mass or more, even more preferably 95% by mass or more, and in some cases even more preferably 99% by mass or more. When the film for producing an optical film of the present invention is substantially composed of the modified PVA, plasticizer, and surfactant, the effects of the present invention can be more fully exhibited.

[0067] (shape, physical properties, etc.) The film for producing an optical film of the present invention is a so-called original film used as a material for an optical film. However, the film for producing an optical film of the present invention is not limited to one in a roll shape.

[0068] The average thickness of the film for optical film production of the present invention is not particularly limited, but the lower limit is preferably 1 μm, more preferably 5 μm, and even more preferably 10 μm. When the average thickness is equal to or greater than the lower limit, it is possible to suppress breakage during uniaxial stretching treatment when producing an optical film. In addition, the upper limit of this average thickness is preferably 75 μm, more preferably 60 μm, even more preferably 45 μm, and even more preferably 35 μm. When the average thickness is equal to or less than the upper limit, it is possible to suppress stretching unevenness during uniaxial stretching treatment. Here, the "average thickness" refers to the average value of thicknesses measured at any five points (hereinafter, the same applies to the average thickness).

[0069] The film for optical film production of the present invention may be a single layer film consisting of one PVA layer (layer containing modified PVA) or a multilayer film containing one PVA layer. However, when used for producing a polarizing film, it is preferable to use a single layer film. The lower limit of the average thickness of the PVA layer in the film for optical film production of the present invention is preferably 1 μm, more preferably 5 μm, and even more preferably 10 μm. By having the average thickness be equal to or greater than the lower limit, it is possible to suppress breakage during uniaxial stretching treatment when producing an optical film. In addition, the upper limit of this average thickness is preferably 75 μm, more preferably 60 μm, more preferably 45 μm, and even more preferably 35 μm. By having the average thickness be equal to or less than the upper limit, it is possible to suppress stretching unevenness during uniaxial stretching treatment.

[0070] For the specific and preferred compositions of the PVA layer in the film for producing an optical film, the above-mentioned specific and preferred compositions of the film for producing an optical film itself can be cited.

[0071] When the film for optical film production of the present invention is a single layer film, the average thickness is preferably 20 μm or more, more preferably 30 μm or more, in order to ensure handling properties, whereas when the film for optical film production of the present invention is a multilayer film, the average thickness of the PVA layer can be 20 μm or less, or 15 μm or less.

[0072] The multilayer film refers to a film having two or more layers. The number of layers of the multilayer film may be 5 or less, or may be 3 or less. The multilayer film may be a film for manufacturing an optical film having a laminated structure of a base resin layer and a PVA layer. The average thickness of the base resin layer is, for example, 20 μm or more and 500 μm or less. The base resin layer in the multilayer film is preferably one that can be uniaxially stretched together with the PVA layer. The resin constituting the base resin layer may be polyester, polyolefin, or the like. Among them, amorphous polyester resin is preferable, and amorphous polyester resin obtained by copolymerizing polyethylene terephthalate with a copolymerization component such as isophthalic acid or 1,4-cyclohexanedimethanol is preferably used. An adhesive layer may be provided between the base resin layer and the PVA layer.

[0073] The width of the film for optical film production of the present invention is not particularly limited and can be determined depending on the application. For example, the lower limit of the width of the film for optical film production is preferably 3 m. In recent years, the screen size of liquid crystal televisions and liquid crystal monitors has been increasing, so if the width of the film for optical film production is set to 3 m or more, it is suitable for applications in which these are used as final products. On the other hand, the upper limit of the width of the film for optical film production is preferably 7 m. By setting the width to 7 m or less, when producing an optical film using a practical device, it is possible to efficiently perform uniaxial stretching processing.

[0074] The swelling degree of the film for optical film production of the present invention is preferably in the range of 140% to 400% in terms of the productivity and optical performance of the optical film. The lower limit of the swelling degree is more preferably 180%, and even more preferably 190%. The upper limit of the swelling degree is more preferably 220%, and even more preferably 210%. The swelling degree of the film can be adjusted to a smaller value, for example, by increasing the heat treatment conditions.

[0075] Here, the "degree of swelling of the film" refers to a value calculated by the following formula. Swelling degree (%)=100×N / M In the formula, N represents the mass (g) of a sample taken from the film after immersing it in distilled water at 30°C for 30 minutes and removing the surface water, and M represents the mass (g) of the sample after drying it in a dryer at 105°C for 16 hours.

[0076] The film for optical film production of the present invention is usually a film that is not substantially stretched (non-stretched film, unstretched film). The in-plane retardation of the film for optical film production is preferably 100 nm or less, more preferably 50 nm or less. Usually, the film for optical film production of the present invention can be stretched (uniaxial stretching or biaxial stretching) to obtain an optical film.

[0077] According to the film for optical film production of the present invention, when producing an optical film having the same shrinkage stress, the stretching temperature is suppressed from being elevated, and an optical film having excellent optical performance can be obtained. The optical performance includes light transmittance, polarization property, etc. Examples of optical films that can be produced using the film for optical film production include polarizing films, retardation films, viewing angle improving films, brightness improving films, etc., and polarizing films are preferred.

[0078] <Method of manufacturing film for optical film production> The method for producing the film for optical film production of the present invention is not particularly limited, but a method that makes the thickness and width of the film more uniform after film production can be preferably adopted. For example, it can be produced using a film-forming solution in which modified PVA and, if necessary, one or more of plasticizers, surfactants, and other additives are dissolved in a liquid medium. When the film-forming solution contains at least one of plasticizers, surfactants, and other additives, it is preferable that these components are mixed uniformly.

[0079] Examples of liquid media used to prepare the film-forming solution include water, dimethyl sulfoxide, dimethylformamide, dimethylacetamide, N-methylpyrrolidone, ethylene glycol, glycerin, propylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, trimethylolpropane, ethylenediamine, and diethylenetriamine, and one or more of these can be used. Among these, water is preferred from the viewpoints of environmental load and recovery. In addition, the above-mentioned modified PVA has good water solubility, and the increase in viscosity when it is made into an aqueous solution at a relatively high temperature (e.g., 80°C) is suppressed. From this viewpoint, water can be preferably used as the liquid medium.

[0080] The volatile content of the film-forming solution (the content in the film-forming solution of volatile components such as liquid mediums that are removed by volatilization or evaporation during film formation) is, for example, preferably 50% by mass to 95% by mass, more preferably 55% by mass to 90% by mass, and even more preferably 60% by mass to 85% by mass. By having the volatile content of the film-forming solution be 50% by mass or more, the viscosity of the film-forming solution does not become too high, and filtration and degassing during preparation of the film-forming solution are smoothly performed, making it easy to produce a film with few foreign matter or defects. On the other hand, by having the volatile content of the film-forming solution be 95% by mass or less, the concentration of the film-forming solution does not become too low, making it easy to produce a film industrially.

[0081] The temperature of the film-forming solution during film formation can be, for example, from 60° C. to 150° C., and preferably from 70° C. to 130° C. By using modified PVA and forming the film at such a relatively high temperature, the viscosity of the film-forming solution can be kept relatively low, and film formability can be improved.

[0082] Examples of the film-forming method when forming a film using the film-forming solution include cast film-forming method, extrusion film-forming method, wet film-forming method, and gel film-forming method. These film-forming methods may be used alone or in combination of two or more. Among these film-forming methods, cast film-forming method and extrusion film-forming method are preferred because they can obtain a film with uniform thickness and width and good physical properties. The formed film can be dried or heat-treated as necessary.

[0083] Specific examples of the manufacturing method of the film for optical film manufacturing of the present invention include the following. Using a T-type slit die, a hopper plate, an I-die, a lip coater die, or the like, the film-forming solution is uniformly discharged or cast onto the peripheral surface of a heated first roll (or belt) located on the most upstream side. The volatile components are evaporated from one side of the film discharged or cast onto the peripheral surface of the first roll (or belt) to dry it. Then, the film is further dried on the peripheral surface of one or more heated rotating rolls arranged downstream, or further dried by passing through a hot air dryer. After that, the film is wound up by a winding device. Drying by a heated roll and drying by a hot air dryer may be performed in combination as appropriate.

[0084] When the film for optical film production of the present invention is a multilayer film, the multilayer film can be produced, for example, by applying a film-forming solution onto a base resin film (base resin layer). At this time, in order to improve the adhesion between the PVA layer and the base resin layer, the surface of the base resin film may be modified or an adhesive may be applied to the surface of the base resin film.

[0085] <Method of manufacturing optical film> The method for producing an optical film of the present invention includes a step of uniaxially stretching the above-mentioned film for producing an optical film. Hereinafter, a method for producing a polarizing film will be specifically described as an example of the method for producing an optical film.

[0086] Examples of the method for producing a polarizing film include a dyeing step for dyeing a film for producing an optical film (hereinafter also referred to as a "PVA film"), a stretching step for uniaxial stretching, and, if necessary, a swelling step for swelling, a crosslinking step for crosslinking, a fixing step for fixing, a cleaning step for cleaning, a drying step for drying, a heat treatment step for heat treatment, and the like. In this case, the order of each step is not particularly limited, and for example, the steps can be performed in the order of a swelling step, a dyeing step, a crosslinking step, a stretching step, and a fixing step. In addition, one or more steps can be performed simultaneously, and each step can be performed twice or more times.

[0087] The swelling step can be carried out by immersing the PVA film in water. The temperature of the water during immersion is preferably 20°C or more and 55°C or less, more preferably 22°C or more and 50°C or less, and even more preferably 25°C or more and 45°C or less. The time for immersion in water is preferably, for example, 0.1 minutes or more and 5 minutes or less, and more preferably 0.5 minutes or more and 3 minutes or less. The water used for immersion in water is not limited to pure water, and may be an aqueous solution in which various components are dissolved, or a mixture of water and an aqueous medium.

[0088] The dyeing process can be carried out by contacting the PVA film with a dichroic dye. An iodine-based dye is generally used as the dichroic dye. The timing of dyeing may be any stage before, during, or after uniaxial stretching. A method of dyeing the PVA film by immersing it in a dye bath containing iodine and potassium iodide (particularly an aqueous solution) is preferably used. The concentration of iodine in the dye bath is preferably 0.01% by mass to 0.5% by mass, and the concentration of potassium iodide is preferably 0.01% by mass to 10% by mass. The temperature of the dye bath is preferably 20° C. to 50° C., particularly preferably 25° C. to 40° C. The preferred dyeing time is 0.2 minutes to 5 minutes.

[0089] By carrying out a crosslinking process for crosslinking the modified PVA in the PVA film, it is possible to effectively prevent the modified PVA from dissolving into water during wet stretching at high temperatures. From this viewpoint, it is preferable to carry out the crosslinking process after the dyeing process and before the stretching process. The crosslinking process can be carried out by immersing the PVA film in an aqueous solution containing a crosslinking agent. As the crosslinking agent, one or more boron compounds such as boric acid and borax or other borates can be used. The concentration of the crosslinking agent in the aqueous solution containing the crosslinking agent is preferably 1% by mass to 15% by mass, more preferably 1.5% by mass to 7% by mass, and even more preferably 2% by mass to 6% by mass. By keeping the concentration of the crosslinking agent within the above range, sufficient stretchability can be maintained. The aqueous solution containing the crosslinking agent may contain potassium iodide or the like. The temperature of the aqueous solution containing the crosslinking agent is preferably 20° C. to 60° C., particularly 25° C. to 55° C. By keeping the temperature within the above range, crosslinking can be efficiently carried out.

[0090] The stretching process for uniaxially stretching the PVA film may be performed by either a wet stretching method or a dry stretching method. In the case of the wet stretching method, it may be performed in an aqueous solution containing boric acid, or in the dye bath described above or in a fixing treatment bath described below. In the case of the dry stretching method, the stretching may be performed at room temperature, or may be performed while heating, or may be performed in air using the PVA film after absorbing water. Among these, the wet stretching method is preferred because it can be stretched with high uniformity in the width direction, and it is more preferred to perform uniaxial stretching in an aqueous solution containing boric acid. The concentration of boric acid in the aqueous solution of boric acid is preferably 0.5% by mass or more and 6.0% by mass or less, more preferably 1.0% by mass or more and 5.0% by mass or less, and particularly preferably 1.5% by mass or more and 4.0% by mass or less. In addition, the aqueous solution of boric acid may contain potassium iodide, and the concentration of potassium iodide is preferably 0.01% by mass or more and 10% by mass or less. The stretching temperature in the uniaxial stretching is preferably 30°C or more and 90°C or less, more preferably 40°C or more and 80°C or less, further preferably 50°C or more and 75°C or less, and particularly preferably 55°C or more and 68°C or less.

[0091] The stretching ratio in the uniaxial stretching (total stretching ratio from the non-stretched PVA film) is preferably 5 times or more, more preferably 5.5 times or more, from the viewpoint of the polarizing performance of the resulting polarizing film. There is no particular upper limit to the stretching ratio, but the stretching ratio is preferably 8 times or less.

[0092] When a long PVA film is uniaxially stretched, the direction of uniaxial stretching is not particularly limited, and uniaxial stretching in the long direction or uniaxial stretching in the transverse direction can be adopted. Since a polarizing film having excellent polarization performance can be obtained, uniaxial stretching in the long direction is preferred. Uniaxial stretching in the long direction can be performed by using a stretching device equipped with multiple rolls parallel to each other and changing the peripheral speed between the rolls. On the other hand, uniaxial stretching in the transverse direction can be performed using a tenter type stretching machine.

[0093] The maximum stretching stress during the stretching process is 30N / mm 2 It is preferable that the maximum stretching stress is 25 N / mm or less. Here, the maximum stretching stress is the value obtained by dividing the maximum tensile force applied to the PVA film by the cross-sectional area of ​​the raw material PVA film. By reducing the maximum stretching stress, a polarizing film with a small shrinkage stress can be obtained. The maximum stretching stress is more preferably 25 N / mm 2 The maximum elongation stress is usually 1N / mm 2 The maximum stretching stress in the stretching step can be reduced by increasing the stretching temperature.

[0094] In the production of a polarizing film, a fixing process can be performed after the stretching process in order to strengthen the adsorption of the dichroic dye (such as an iodine-based dye) to the PVA film. As the fixing bath used for the fixing process, an aqueous solution containing one or more boron compounds such as boric acid and borax can be used. If necessary, an iodine compound or a metal compound may be added to the fixing bath. The concentration of the boron compound in the fixing bath is preferably 2% by mass or more and 15% by mass or less, particularly preferably 3% by mass or more and 10% by mass or less. By setting the concentration of the boron compound within the above range, the adsorption of the dichroic dye can be made stronger. The temperature of the fixing bath is preferably 15° C. or more and 60° C. or less, particularly preferably 25° C. or more and 40° C. or less.

[0095] The cleaning step is generally performed by immersing the film in distilled water, pure water, an aqueous solution, or the like. In this case, from the viewpoint of improving the polarization performance, it is preferable to use an aqueous solution containing an iodide such as potassium iodide as an auxiliary, and the concentration of the iodide is preferably 0.5% by mass to 10% by mass. The temperature of the aqueous solution in the cleaning process is generally 5° C. to 50° C., preferably 10° C. to 45° C., and more preferably 15° C. to 40° C. By setting the temperature of the aqueous solution within the above range, it is possible to further improve the polarization performance.

[0096] The conditions for the drying step are not particularly limited, but it is preferable to dry the PVA film at a temperature of 30° C. to 150° C., particularly 50° C. to 130° C. Drying at a temperature within this range makes it easier to obtain a polarizing film with excellent dimensional stability.

[0097] In addition, optical films other than polarizing films, such as retardation films, can also be produced by a method including a step of uniaxially stretching the film for producing an optical film of the present invention. As for the specific production method, a conventionally known method can be adopted except that the film for producing an optical film of the present invention is used.

[0098] <Optical film> The optical film of the present invention comprises a PVA having a silicon-containing group and an ethylene unit (modified PVA), wherein the silicon-containing group is a silanol group or a group that can be converted into a silanol group in the presence of water, the content of the silicon-containing group relative to all structural units in the modified PVA is from 0.01 mol % to 1.0 mol %, and the content of the ethylene unit is from 0.5 mol % to 10 mol %.

[0099] The optical film of the present invention may be an optical film obtained by the above-mentioned manufacturing method using the film for optical film manufacturing of the present invention. The specific structure, content, and other details of the modified PVA contained in the optical film of the present invention are the same as those of the modified PVA contained in the film for optical film manufacturing of the present invention. In addition, the optical film of the present invention may contain other components similar to those of the film for optical film manufacturing of the present invention.

[0100] The optical film of the present invention may be a polarizing film, a retardation film, a viewing angle improving film, a brightness improving film, etc., and is preferably a polarizing film. In this case, the polarizing film usually contains a dichroic dye, and the modified PVA may be crosslinked.

[0101] The optical film of the present invention is preferably a stretched film, more preferably a uniaxially stretched film.The optical film of the present invention may be a single-layer film or a multi-layer film, but is preferably a single-layer film.When it is such a film, the optical film of the present invention can be more suitably used as a polarizing film, etc.

[0102] The shrinkage stress of the optical film of the present invention is 100 N / mm 2 The shrinkage stress is preferably 80 N / mm or less. The small shrinkage stress provides excellent dimensional stability even when used at high temperatures. The shrinkage stress is more preferably 80 N / mm 2 The lower limit of the shrinkage stress of the optical film of the present invention is, for example, 10 N / mm 2 20N / mm 2or 40N / mm 2 The shrinkage stress herein refers to a value obtained by dividing the tension when both edges in the stretching direction of a sample polarizing film are fixed and maintained at 80° C. for 4 hours by the cross-sectional area of ​​the sample, and specifically refers to a value obtained by the method described in the Examples below.

[0103] When the optical film of the present invention is a polarizing film, the dichroic ratio (R) of the polarizing film is preferably 100 or more. By including the above-mentioned modified PVA, a polarizing film having such a high dichroic ratio (R) can be produced with good productivity. The dichroic ratio (R) is more preferably 150 or more, further preferably 190 or more, and particularly preferably 200 or more. The upper limit of this dichroic ratio (R) may be, for example, 350, or may be 300 or 250.

[0104] The method for calculating the dichroic ratio (R) of a polarizing film is as follows. First, the relationship between the transmittance (T') excluding surface reflection and the single-piece transmittance (T) is shown in formula (a). In this case, the refractive index of the polarizing film is assumed to be 1.5, and the reflectance at the surface is assumed to be 4%. The relationship between the transmittance (T'), degree of polarization (V), and dichroic ratio (R) is shown in formula (b). Therefore, the dichroic ratio (R) of the polarizing film can be calculated by measuring the single-piece transmittance (T) and degree of polarization (V), and then using these values ​​to solve formulas (a) and (b). T' = T / (1-0.04) 2 (a) R={-ln[T'(1-V)]} / {-ln[T'(1+V)]} ···(b)

[0105] A polarizing film is usually used as a polarizing plate by laminating an optically transparent and mechanically strong protective film on either or both sides of the polarizing film. Examples of protective films that can be used include cellulose triacetate (TAC) film, cycloolefin polymer (COP) film, cellulose acetate butyrate (CAB) film, acrylic film, and polyester film. Examples of adhesives used for lamination include PVA adhesives, urethane adhesives, and acrylate ultraviolet-curing adhesives. In other words, a polarizing plate has a polarizing film and a protective film laminated on either or both sides of the polarizing film directly or via an adhesive layer.

[0106] The polarizing plate can be used as a part of an LCD by, for example, coating it with an acrylic adhesive and then bonding it to a glass substrate. Note that the polarizing plate may further be bonded with a retardation film, a viewing angle improving film, a brightness improving film, etc. EXAMPLES

[0107] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. The methods of measurement and evaluation are as follows.

[0108] [PVA polymerization degree (viscosity average polymerization degree)] For each PVA synthesized in the following synthesis examples, the viscosity average degree of polymerization was measured according to the description of JIS K6726-1994.

[0109] [Saponification degree of PVA] For each PVA synthesized in the following synthesis examples, the degree of saponification was measured according to the description of JIS K6726-1994.

[0110] [Content of silicon-containing groups and ethylene units in PVA] For each PVA synthesized in the following synthesis examples, the content of silicon-containing groups and ethylene units was measured by proton NMR of the vinyl ester polymer before saponification. When measuring the proton NMR of the vinyl ester polymer before saponification, the vinyl ester polymer was purified by reprecipitation with hexane-acetone to completely remove unreacted monomers from the polymer, then dried at 90°C under reduced pressure for 2 days, and then measured by CDCl. 3 The product was dissolved in a solvent and subjected to analysis.

[0111] [Film swelling degree] Each film (film for optical film production) obtained in the following Examples and Comparative Examples was cut to 1.5 g and immersed in 1000 g of distilled water at 30° C. for 30 minutes. After immersion for 30 minutes, the film was taken out, the water on the surface was absorbed with filter paper, and the mass (N) was measured. Then, the film was dried in a dryer at 105° C. for 16 hours, and the mass (M) after drying was measured. The swelling degree of the film was calculated from the obtained mass (N) and mass (M) by the following formula. Swelling degree (%)=100×N / M

[0112] [Dichroic ratio of polarizing film (optical performance)] A rectangular sample of 4 cm in the length direction of the polarizing film was taken from the center in the width direction of each polarizing film obtained in the following Examples and Comparative Examples. The single transmittance (T) and polarization degree (V) of this sample were measured using an integrating sphere spectrophotometer (JASCO Corporation's "V7100") in accordance with JIS Z8722 (measurement method for object color) after luminosity correction in the visible light region with a C light source and a 2° visual field.

[0113] The dichroic ratio (R) of the polarizing film was calculated by solving the following formulas (a) and (b) from the obtained values ​​of single transmittance (T) and polarization degree (V). Here, the refractive index of the polarizing film was set to 1.5, and the reflectance at the surface was set to 4%. The dichroic ratio (R) of the polarizing film manufactured under the temperature conditions of the uniaxial stretching treatment bath in the Examples and Comparative Examples was calculated as R 0 It was decided. T' = T / (1-0.04)2 (a) R={-ln[T'(1-V)]} / {-ln[T'(1+V)]} ···(b)

[0114] [Polarizing film shrinkage stress] The shrinkage stress of each polarizing film obtained in the following examples and comparative examples was measured using Shimadzu Corporation's autograph "AG-X" with a thermostatic chamber and a video extensometer "TR ViewX120S". For the measurement, a polarizing film that had been conditioned at 20°C / 20% RH for 18 hours was used. After the thermostatic chamber of the autograph "AG-X" was set to 20°C, the polarizing film (15 cm in the length direction, 1.5 cm in the width direction) was attached to a chuck (chuck interval 5 cm), and the temperature of the thermostatic chamber was raised to 80°C at the same time as the start of pulling. The stretching direction of the polarizing film was set to the length direction, and the film was pulled in this direction. The polarizing film was pulled at a speed of 1 mm / min, and the pulling was stopped when the tension reached 2 N, and the tension was measured in this state for up to 4 hours. At this time, because the distance between the chucks changes due to thermal expansion, a gauge sticker was attached to the chuck and the measurement was performed using a video extensometer "TR ViewX120S" so that the distance between the chucks could be corrected by the amount of movement of the gauge sticker attached to the chuck. Note that the shrinkage force of the polarizing film was calculated by subtracting the initial tension of 2N from the measured tension after 4 hours, and the shrinkage stress (N / mm 2 The shrinkage stress (SF) of the polarizing film produced under the temperature conditions of the uniaxial stretching bath in the Examples and Comparative Examples was calculated as SF 0 It was decided.

[0115] [Polarizing film shrinkage stress 75N / mm 2 Dichroic ratio and stretching temperature at In the following examples and comparative examples, polarizing films with different uniaxial stretching bath temperatures were obtained in the same manner, except that the temperature of the uniaxial stretching bath was 2°C or 4°C lower, and the iodine concentration of the dyeing bath was changed so that the transmittance of the obtained polarizing film was 44.0%. The single transmittance (T) and polarization degree (V) of each obtained polarizing film were measured, and the dichroic ratio (R) was calculated by the above-mentioned method. Here, the dichroic ratio (R) of the polarizing film obtained under the condition where the temperature of the uniaxial stretching bath was 2°C lower was defined as R -2 The dichroic ratio (R) of the polarizing film obtained under the condition where the temperature of the uniaxial stretching bath is 4°C lower is R -4 The shrinkage stress of each polarizing film was measured by the above-mentioned method. Here, the shrinkage force (SF) of the polarizing film obtained under the condition that the temperature of the uniaxial stretching treatment bath was 2°C lower was SF -2 The shrinkage force (SF) of the polarizing film obtained under the condition that the temperature of the uniaxial stretching treatment bath is 4°C lower is SF -4 It was decided.

[0116] The dichroic ratios (R 0 , R -2 , R -4 ) and shrinkage stress (SF 0 ,SCIENCE FICTION -2 ,SCIENCE FICTION -4 ) and the relationship between the dichroic ratio and the shrinkage stress was plotted, and a linear approximation was used to determine a shrinkage stress of 75 N / mm 2 The dichroic ratio at a shrinkage stress of 75 N / mm was calculated. 2 The stretching temperature at

[0117] [Synthesis Example 1] Synthesis of PVA-1 A 5L pressurized reaction vessel equipped with a stirrer, a nitrogen inlet, an ethylene inlet, an initiator addition port, and a delay solution addition port was charged with 3000g of vinyl acetate and 3.6g of vinyltrimethoxysilane as a monomer having a silicon-containing group, and the temperature was raised to 60°C, after which the system was replaced with nitrogen by nitrogen bubbling for 30 minutes. Ethylene was then introduced so that the reaction vessel pressure was 0.26MPa. After the temperature inside the polymerization vessel was adjusted to 60°C, 1.0g of 2,2'-azobisisobutyronitrile (AIBN) was injected to start polymerization. During polymerization, ethylene was introduced to maintain the reaction vessel pressure at 0.26MPa and the polymerization temperature at 60°C while injecting a 2% by mass methanol solution of vinyltrimethoxysilane, and the polymerization was stopped by cooling when the polymerization rate reached 20% after 3 hours. The amount of the methanol solution of vinyltrimethoxysilane added by the end of polymerization was 84ml. Next, unreacted vinyl acetate was removed under reduced pressure to obtain a methanol solution of modified polyvinyl acetate (hereinafter sometimes abbreviated as modified PVAc). The concentration of the obtained methanol solution of modified PVAc was adjusted to 23.5% by mass, and NaOH methanol solution (10% by mass concentration) was added so that the alkali molar ratio (moles of NaOH / moles of vinyl ester units in modified PVAc) became 0.04, and saponification was performed. The obtained polyvinyl alcohol was washed with methanol. The degree of polymerization (viscosity average degree of polymerization) of PVA-1 obtained by the above operations was 3,300, the degree of saponification was 99.9 mol%, the content of silicon-containing groups was 0.2 mol%, and the content of ethylene units was 2.5 mol%.

[0118] [Synthesis Examples 2-9] Synthesis of PVA-2 to PVA-9 PVA-2 to PVA-9 having the viscosity average degree of polymerization, degree of saponification, silicon-containing group content, and ethylene unit content shown in Table 1 were obtained in accordance with Synthesis Example 1 while appropriately adjusting the ratio of the monomers used, the polymerization conditions, and the saponification conditions.

[0119] [Example 1] An aqueous solution containing 100 parts by mass of PVA-1, 10 parts by mass of glycerin as a plasticizer, and 0.1 parts by mass of sodium polyoxyethylene lauryl ether sulfate as a surfactant, and having a PVA content of 9.5% by mass, was prepared as a film-forming solution. This film-forming solution was dried on a metal roll at 80°C, and the resulting film was heat-treated in a hot air dryer at a temperature of 105°C for 10 minutes to adjust the swelling degree to 200%, and a PVA film (film for optical film production) with an average thickness of 30 μm was produced.

[0120] A sample of 5 cm wide x 9 cm long was cut from the center of the width direction of the obtained PVA film so that a range of 5 cm wide x 5 cm long could be uniaxially stretched. This sample was immersed in pure water at 30 ° C for 60 seconds, uniaxially stretched 2.0 times in the length direction, and swollen. Next, it was immersed in an aqueous solution containing 0.05 mass % iodine and 1.15 mass % potassium iodide (dyeing treatment bath: temperature 32 ° C) for 120 seconds, and uniaxially stretched 1.2 times (total 2.4 times) in the length direction to adsorb iodine. Next, it was immersed in an aqueous solution containing 2.6 mass % boric acid (boric acid crosslinking treatment bath: temperature 32 ° C) for 120 seconds, and uniaxially stretched 1.25 times (total 3.0 times) in the length direction. The film was then immersed in an aqueous solution (uniaxial stretching bath) at 69° C. containing 2.8% by mass of boric acid and 5% by mass of potassium iodide, and uniaxially stretched in the length direction to a total of 6.0 times. The film was then washed by immersing for 5 seconds in an aqueous solution (washing bath) at 22° C. containing 1.5% by mass of boric acid and 3.5% by mass of potassium iodide. Finally, the film was dried at 80° C. for 4 minutes to obtain a polarized film.

[0121] The obtained polarizing film was subjected to the above-mentioned method to obtain a polarizing film with a shrinkage stress of 75 N / mm 2 The dichroic ratio was calculated by the above-mentioned method. 2 The stretching temperature was determined. The results are shown in Table 1 and FIG.

[0122] [Examples 2 to 3 and Comparative Examples 1 to 5] The PVA films were produced and evaluated in the same manner as in Example 1, except that the PVA content in the film-forming solution and the heat treatment temperature were adjusted using the PVAs (PVA-2 to PVA-8) shown in Table 1 so that the average thickness of the PVA film was 30 μm and the swelling degree was 200%. The shrinkage stress of the resulting polarizing film was 75 N / mm 2 A polarizing film was produced and evaluated in the same manner as in Example 1, except that the temperature of the uniaxial stretching treatment bath and the iodine concentration of the dyeing treatment bath were changed so that the single transmittance before and after the stretching was 44.0%. The results are shown in Table 1 and Figures 1 and 2.

[0123] [Comparative Example 6] We tried to make a film-making solution using PVA-9 as PVA, but the PVA did not dissolve, and we were unable to make a film-making solution. As a result, we were unable to produce PVA film and polarizing film, and the shrinkage stress of the polarizing film was 75N / mm 2 The dichroic ratio and stretching temperature at the same time could not be measured.

[0124] [Table 1]

[0125] As shown in Table 1 and FIG. 1, the films for producing optical films (PVA films) of Examples 1 to 3 had a shrinkage stress of 75 N / mm 2 When manufacturing an optical film having a dichroic ratio of 200 or more, an optical film can be obtained at a stretching temperature of 68° C. or less. That is, when manufacturing an optical film having the same shrinkage stress, the films for manufacturing an optical film of Examples 1 to 3 can suppress an increase in the stretching temperature and can obtain an optical film having excellent optical performance. In other words, the films for manufacturing an optical film of Examples 1 to 3 can suppress an increase in the shrinkage stress and an increase in the stretching temperature while improving the optical performance of the obtained optical film.

[0126] As shown in Figure 2, when films for producing optical films (PVA films) using PVA with the same degree of polymerization are compared, the following can be seen. Compared to Comparative Example 1, which used unmodified PVA with a degree of polymerization of 2400, Comparative Examples 4 and 5, which used modified PVA with a degree of polymerization of 2400 and a silicon-containing group content of 0.2 mol % or 0.4 mol %, had a shrinkage stress of 75 N / mm 2 Although the dichroic ratio (optical performance) is remarkably increased in the case of unmodified PVA, the stretching temperature is also significantly increased. In other words, compared with the case of using unmodified PVA, the PVA film using PVA having only silicon-containing groups can significantly improve the optical performance of the obtained optical film, but it is not possible to suppress the stretching temperature from being raised. On the other hand, in Example 3, which used modified PVA with a degree of polymerization of 2400, a silicon-containing group content of 0.2 mol %, and an ethylene unit content of 4.5 mol %, the shrinkage stress was 75 N / mm 2 The dichroic ratio (optical performance) in Comparative Example 1 is increased compared to Comparative Example 4, while the stretching temperature is almost the same and the stretching temperature is suppressed from increasing. That is, compared to the case where PVA having only silicon-containing groups is used, when an optical film having the same shrinkage stress is produced, the optical film production film (PVA film) using PVA having silicon-containing groups and ethylene units suppresses the stretching temperature from increasing and can obtain an optical film with excellent optical performance. In other words, the optical performance of the obtained optical film can be improved while suppressing an increase in shrinkage stress and an increase in the stretching temperature. [Industrial Applicability]

[0127] The film for producing an optical film of the present invention can be suitably used as a material for polarizing films, which are constituent materials of LCDs.

Claims

1. A method for producing a polarizing film, comprising the steps of uniaxially stretching a film for producing a polarizing film, The film for producing a polarizing film is It comprises a polyvinyl alcohol having a silicon-containing group and an ethylene unit, the silicon-containing group is a silanol group or a group that can be converted to a silanol group in the presence of water; the content of the silicon-containing group relative to all structural units in the polyvinyl alcohol is from 0.01 mol % to 1.0 mol %, and the content of the ethylene unit is from 0.5 mol % to 10 mol %.

2. The method for producing a polarizing film according to claim 1 , wherein the polyvinyl alcohol has a viscosity average degree of polymerization of 1,000 or more and 6,000 or less and a degree of saponification of 98.7 mol % or more.

3. The method for producing a polarizing film according to claim 2 , wherein the product of the viscosity average degree of polymerization and the content of the silicon-containing group is 100 mol % or more and 2,000 mol % or less.

4. A method for producing a polarized film described in any one of claims 1 to 3, wherein the average thickness of the film for producing a polarized film is 1 μm or more and 75 μm or less.

5. A method for producing a polarized film described in any one of claims 1 to 4, wherein the swelling degree of the film for producing a polarized film is 140% or more and 400% or less.

6. A method for producing a polarized film described in any one of claims 1 to 5, wherein the film for producing a polarized film is a non-stretched film.

7. It comprises a polyvinyl alcohol having a silicon-containing group and an ethylene unit, the silicon-containing group is a silanol group or a group that can be converted to a silanol group in the presence of water; the content of the silicon-containing group relative to all structural units in the polyvinyl alcohol is from 0.01 mol % to 1.0 mol %, and the content of the ethylene unit is from 0.5 mol % to 10 mol %.

8. Shrinkage stress is 100N / m 2 The polarizing film of claim 7 , wherein:

9. The polarizing film according to claim 7 or 8, which is a single layer film.

Citation Information

Patent Citations

  • Polarization film and its manufacture

    JP1989105204A

  • Polyvinyl alcohol film

    JP1996188624A

  • Production of gas barrier film

    JP2000318034A

  • Water-resistant composition

    JP2001139750A

  • Polyvinyl alcohol film for optical film, its manufacturing method and polarizing film and polarizing plate obtained using the same

    JP2007009056A